PERAN STRATEGIS PEMUDA DALAM MITIGASI BENCANA DI INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Yonatan Yolius Anggara; Dyah Respati Suryo Sumunar; Nursida Arif; Rosyid Shidiq Hidayatulloh (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2025)
Abstract: Indonesia, as a disaster-prone country, requires effective disaster mitigation efforts. Youth participation in disaster mitigation has increased significantly over the past few decades, marked by their involvement in various preparedness activities and policy advocacy. This study aims to identify, analyze, and summarize the contributions of youth in disaster mitigation, as well as explore the supporting factors and challenges they face, through a systematic literature review. The findings indicate that youth play an important role across several scales: individual scale, pre-disaster, during disaster, post-disaster, and community scale. The factors driving youth involvement include system support, individual capacity, as well as motivation and active participation. However, there are challenges that hinder youth engagement, such as limited resources, system weaknesses, and a lack of awareness and participation from the community. This study recommends developing community-based disaster mitigation and utilizing social media as a campaign tool. These findings underscore the importance of empowering youth to play an active role in disaster mitigation in a more structured and sustainable manner.